Does Self-Management Affect Students' Digital Literacy? Evidence from a Campus in Riau Province - Ririen, Deci; Heriasman, Heriasman (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2021)
This study aims to analyze the influence of self management consisting of self motivation, self organizing and self control on students' digital literacy. This research is a quantitative study of multiple correlation regression type, the subject of this research is STIE Indragiri students, totaling 234 people. The research instrument developed in this study was a closed questionnaire. The data analysis technique used regression analysis multiple linear with the help of SPSS 24. The results showed that self-management had a effect on students' digital literacy. The details for each component of self-management show that: Self motivation ability has a significant effect on students' digital literacy. Self-organizingl ability has no significant effect on students' digital literacy. Self-control ability has a significant effect on students' digital literacy. Among the three independent variables that have the most influence on students' digital literacy is the ability to self-motivation. Self-motivation has an important role in encouraging humans to act, determining the direction of action and selecting actions to determine what actions are chosen to achieve goals, these various abilities are in accordance with the abilities that must be met to improve digital literacy skills.